2 + 2 = 3: Number contrasts in Blackfoot. Issue 1 (1st November 2017) - Kim, Kyumin; Ritter, Elizabeth; Wiltschko, Martina; Rullmann, Hotze
Abstract : Blackfoot nominals are singular, plural or general in number. The existence of languages with either a singular-plural opposition or a plural-general opposition is well-attested in the literature. Following Bliss (2013 ), we argue that Blackfoot has both systems, albeit in different contexts. We propose that the co-existence of these two systems in Blackfoot is due to the exceptional nature of plural specification in this language – it is alternatively realized as a head or modifying feature in the syntactic representation (in the sense of Wiltschko 2008 ). We show that regardless of whether plural is syntactically a head or a modifying feature, the semantic interpretation is the same. This is consistent with Rullmann & You's (2006 ) finding that plural marking has the same denotation no matter whether it contrasts with singular or with general number.